WATER BALANCE ANALYSIS OF TAILING STORAGE FACILITY FOR MINE CLOSURE ACTIVITIES - Anshari Akbar, M.
Tailings Storage Facility (TSF), which is the media for tailings disposal, is closely related to the environmental and social impacts and risks arising from these tailings storage facilities. One of the impacts on TSF is related to surface water which must be managed properly. Of greatest concern is the water balance in the TSF. Therefore it is necessary to analyze several hydrological parameters to determine the difference between the volume of water entering and the volume of water out of the TSF, so that the mine closure method of handling TSF can reduce the risk of environmental pollution. Analysis of the rain parameters using the Partial Duration Series (PDS) method was carried out to calculate the water discharge that must be managed in an open channel and additional analysis for potential evaporation parameters to calculate the mine closure TSF fill. The method of selecting the maximum daily rainfall data becomes the data used to analyze the need for open drainage facilities. Meanwhile, for TSF filling during mine closure, scenarios of extreme conditions are made for potential rainfall and evaporation parameters which are then analyzed to determine the water balance. Based on the results of the analysis of the maximum daily data, it is found that the amount of water discharge that must be managed in an open drainage facility is 1.511 m3 / s. Meanwhile, for TSF filling, it was found that the fastest scenario required 31.8 months and vice versa for the longest charging scenario, it took 110.4 months. To determine the mine closure TSF handling method, the results of water balance analysis for several scenarios of climatic conditions resulted in the minimum thickness of the water column in the TSF ranging from 6 - 8 m. Based on the results of water balance analysis for several scenarios of climate conditions on the TSF, the method of handling TSF during mine closure is by using wet cover.